Capillary microsampling of whole blood for mouse PK studies: an easy route to serial blood sampling. (March 2015) - Korfmacher, Walter; Fitzgerald, Maria; Luo, Yongyi; Ho, Stacy; Wang, Jie; Wu, Zhongtao; Snow, Gregory; O'Shea, Thomas
Background: Capillary microsampling (CMS) of 8 µl of blood provides a methodology that can be utilized for serial sampling in drug discovery mouse PK studies.Results: Blood CMS sample results were compared to plasma sample results for three compounds (with expected Cb/Cp of 1 to 2) and found to be similar. In addition, for three compounds, blood CMS results were found to be equivalent to results generated with standard whole blood sampling. In a 5-day repeated dose PK study, four mice were dosed (IV) daily and sampled on both day one and day five using blood CMS procedure.Conclusion: Blood CMS using 8 µl glass capillary microsamples provides a straightforward and effective approach for mouse serial blood sampling.